Struktur Modal dan Pengaruhnya Terhadap Profitabilitas Perusahaan (Studi Pada Perusahaan JII-30) - Nurharyati Panigoro (Program Studi S1 Akuntansi Jurusan Akuntansi, Fakultas Ekonomi Universitas Negeri Gorontalo, 2020)
The purpose of this research is to determine the capital structure owned by the company and its impact on company profitability. The sample used is companies incorporated in the JII index in the December 2018-May 2019 period. The data used are financial statements in 2019. The variables observed in this study are capital structure variables represented by the LTDA ratio (Long Term Debt to Total Assets) and DER (Debt to Equty Ratio) as the independent variable and ROE (Return on Equity) as the dependent variable. Research conducted on 30 companies included in the JII index shows that there is a significant influence of LTDA and DER variables on company ROE. Judging from the form of influence, LTDA variable gives a negative influence on ROE while the DER variable gives a positive effect on ROE